Geometry relaxation-mediated localization and delocalization of excitons in organic semiconductors: a quantum chemical study - Deutsch, Marian; Wirsing, Sara; Kaiser, Dustin; Fink, Reinhold F.; Tegeder, Petra; Engels, Bernd (The journal of chemical physics, 2020)
Photo-induced relaxation processes leading to excimer formations or other traps are in the focus of many investigations of optoelectronic materials because they severely affect the efficiencies of corresponding devices. Such relaxation effects comprise inter-monomer distortions in which the orientations of the monomer change with respect to each other, whereas intra-monomer distortions are variations in the geometry of single monomers. Such distortions are generally neglected in quantum chemical investigations of organic dye aggregates due to the accompanied high computational costs. In the present study, we investigate their relevance using perylene-bisimide dimers and diindenoperylene tetramers as model systems. Our calculations underline the importance of intra-monomer distortions on the shape of the potential energy surfaces as a function of the coupling between the monomers. The latter is shown to depend strongly on the electronic state under consideration. In particular, it differs between the first and second excited state of the aggregate. Additionally, the magnitude of the geometrical relaxation decreases if the exciton is delocalized over an increasing number of monomers. For the interpretation of the vibronic coupling model, pseudo-Jahn-Teller or Marcus theory can be employed. In the first part of this paper, we establish the accuracy of density functional theory-based approaches for the prediction of vibrationally resolved absorption spectra of organic semiconductors. These investigations underline the accuracy of those approaches although shortcomings become obvious as well. These calculations also indicate the strength of intra-monomer relaxation effects.